Modifying Gobak Sodor into A Learning Medium for Improving Students' Scientific Attitude - Ulia Anisatur Rosidah; Miftakhul Huda; Johann Hofer (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2022)
This study aims to improve scientific attitudes by modifying Gobak Sodor, a team-based game in which two teams of three members each attempt to beat one another. One team plays as the defender, while another team acts as the attacker in a square field with boundaries usually marked by chalk. This qualitative study collected the data by observation and documentation, finding that 9 out of 10 2nd-grade students in MI Ma'aruf NU Metro exhibited better attitudes, including honesty, cooperation, optimism, objectivity, and tolerance. Despite the attitudinal improvements made, a number of aspects, including social awareness, courage to express opinion, creativity, and innovation, needed further improvement. This game was proven to be interesting for lower-grade elementary school students. The game could also be played without any special tools, allowing students to develop their scientific attitudes throughout the game.